Pengaruh Gender Dan Tipe Kepribadian Dalam Kompetensi Menyimak - Aida Azizah; Evi Chamalah; Turahmat Turahmat; Cahyo Hasanudin; Ana Yudhika Aidatuz Zumara (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
One of the key processes in communication is listening. Listening is a language skill that can broaden one’s horizons when done well and correctly. Gender refers to the observable differences in society between men and women; it is not innate and can change over time. Every individual has a distinct personality, which is categorized into two types: extroverted and introverted. The researcher conducted this study after observing differences in listening outcomes between women and men with diverse personalities during learning activities in a university setting. The purpose of this study is to examine the influence of gender (male and female) and personality types (introvert and extrovert) on the listening competence of students in the Indonesian Language and Literature Education Program, FKIP, Unissula. This quantitative study employed an experimental design involving 60 students using a simple 2 x 2 factorial design. This study employed linear regression analysis to examine the influence of the variables under investigation. The hypotheses for this study consist of Ho, which states that there is no significant interaction between gender and personality type in students’ listening skills, and Ha, which states that there is a significant interaction between gender and personality type in students’ listening skills. The results of the study indicate that, in general, there is a positive interaction between gender and personality type regarding students’ listening competence. This interaction is evident from the statistical calculations, which show that the calculated F-value is 3.619, which is greater than the critical F-value of 3.072. The findings reveal that female students with an extroverted personality type demonstrate better listening performance compared to others. Furthermore, there is a relationship between gender and personality that can influence students’ listening performance. Therefore, it can be concluded that there is an interaction between these two variables regarding students’ listening competence, and thus the alternative hypothesis (Ha) is accepted.